The determinant of dividend payment by Tabung Haji / Nursazreena Azwa Nasaruddin and Naazira Jamaludin - Nasaruddin, Nursazreena Azwa; Jamaludin, Naazira (Faculty of Business and Management, 2019)
This study attempt to identify the factor that effect the changes dividend payment on Tabung Haji in Malaysia. The variables we used for this study are crude palm oil, crude oil price, stock market and exchange rate. These variables are only external variable and not intend to examine the firm-specific factor. As we all known, the external factors like macroeconomic variables cannot be simply ignored by investor or depositor as they could give an impact towards dividend payment for such firm. In order to accomplish the set of objectives of this study, the data was tested by time series which used 33 years of data from 1984 to 2017 all variables. The Single linear regression, Multiple linear regression, Ordinary Least Square (OLS) method and Diagnostic test used to analyze the all variables. Based on the result, which refer to regression on multiple linear regression, only crude palm oil has positive significant towards dividend payment, while other variables are insignificant. The finding of the study could be useful for the potential depositor in order to find new avenue to enjoy a good passive income with lowest risk of default.